Smart grid - communication-enabled intelligence for the electric power grid - Bush, Stephen F. (Chichester, West Sussex, [England] : Wiley / IEEE, 2014)
"This book explores the smart grid from generation to consumption; both as it is planned today and how it will likely evolve tomorrow"--
Electric power systems: the main component -- Communication and networking: the enabler -- Embedded and distributed intelligence for a smart grid: the ultimate goal.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Smart power grids; TECHNOLOGY & ENGINEERING / Power Resources / General; Smart power grids; Electronic books; Electronic books